2014
DOI: 10.9790/2380-07933338
|View full text |Cite
|
Sign up to set email alerts
|

Protein Characterization of Extracted Water from Three Kinds of Edible Bird Nest Using SDS-PAGE CBB Staining and SDSPAGE Glycoprotein Staining and LC-MS/MS Analyses

Abstract: Abstract:The objective of this research is to see the comparison of protein characterization from three kinds of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…This is also due to the 7.0 KDa cut-off molecular weight of the dialysis tubing used to separate the mixture. The protein size of EBN extract was 140.8, 64.8, and 21.1 kDa, whereas the molecular weight of EBN glycoprotein was 140.8 and 64.8 kDa [39]. Raw EBNs depict more and distinct bands as compared to processed EBNs, where the EBN processing may have reduced the original amount of intact protein, thus resulting in different protein profiles [4].…”
Section: Molecular Weight Distribution Of Protein In Extracts and Hydrolysates Of Ebnsmentioning
confidence: 99%
“…This is also due to the 7.0 KDa cut-off molecular weight of the dialysis tubing used to separate the mixture. The protein size of EBN extract was 140.8, 64.8, and 21.1 kDa, whereas the molecular weight of EBN glycoprotein was 140.8 and 64.8 kDa [39]. Raw EBNs depict more and distinct bands as compared to processed EBNs, where the EBN processing may have reduced the original amount of intact protein, thus resulting in different protein profiles [4].…”
Section: Molecular Weight Distribution Of Protein In Extracts and Hydrolysates Of Ebnsmentioning
confidence: 99%
“…Hasil yang diperoleh dari protein SBW setelah dicerna hampir mirip dengan protein serum sapi yang mencapai tingkat kecernaan 95% (Deutz et al, 1995). Berat molekul protein SBW bervariasi, sekitar 140,8, 64,8 dan 21,2 kDa (Utomo et al 2014). Sebagian besar protein berukuran besar dicerna menjadi 70 kDa, 40 kDa dan di bawahnya, sementara beberapa protein besar lainnya tetap stabil (Xian et al, 2010).…”
Section: Sifat Fisikokimia Bahan Bioaktif Sarang Burung Waletunclassified
“…No. Monosaccharide Kathan & Weeks [33] Tung et al [34] Chua et al [35] [41] Purification of house EBN's sialyl-glycoprotein showed the abundance molecular weight of 128 kDa (19.1%), 106 kDa (18.5%) and 43 kDa (29.4%). The sialyl-glycoprotein with 43 kDa contained terminal α2-3 and α2-6 sialic acid linkage.…”
Section: Nomentioning
confidence: 99%